Identifying strategies to advance equitable implementation of co-occurring mental health and substance use disorder treatment in drug treatment courts: A study protocol - Ayorkor Gaba; Ashleigh LoVette; Bailey Pridgen; Marquita Taylor; Eva Woodward; Milagros C. Rosal; Melissa Anderson; David Smelson (Journal of Clinical and Translational Science, 2023)
Abstract